Asssesing the Students' Needs on the Use of E Modules in Learning English at High Schools - Dewi, Yosa Novia; Rozimela, Yenni; Zaim, M; Masoud, Hamad Msamaa (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to analyze the extent of students' needs for the use of e-modules in English subjects at high schools. Analyzing students' needs for learning media is a process carried out to identify the needs and characteristics of individual students to develop appropriate learning programs by utilizing suitable learning media. In analyzing students' needs for learning media, it is important to consider various factors, such as the most effective and efficient type of learning media to achieve learning goals, students' interests and preferences for learning media, and students' technological abilities. This research is quantitative and was conducted in 2023. The study sample consisted of students from three high schools in West Sumatra. The research instrument was a questionnaire consisting of 42 statements to analyze students' needs, covering three main aspects: (1) Necessities: Language aspects that students must master, (2) Lacks: Language aspects that students have and have not mastered, (3) Wants: Language aspects that students want to learn. The questionnaire used a Likert scale with four response categories: very needed, needed, not needed, and very not needed. Data were analyzed using the class interval technique to categorize the results. The findings revealed that English language skills are highly needed by students, and they are eager to master them. Additionally, English learning media is considered essential by students to support their learning process. The types of learning media students desire include: (1) Electronic learning media that can improve English language skills, (2) Media that utilizes audio-visual elements, (3) Media that is flexible, accessible anytime and anywhere. These results emphasize the importance of developing learning media that aligns with students' needs and preferences to enhance the effectiveness of English learning in high schools.